Electrochemical Characterization of Az31 Magnesium Alloy Treated by Ultrasonic Impact Peening (Uip) - Daniel Kajanek; Branislav Hadzima; Filip Pastorek (Communications - Scientific letters of the University of Zilina, 2018)
Electrochemical characteristics of AZ31 magnesium alloy after impacting by ultrasonic impact peening (UIP) were measured in order to evaluate its effect on corrosion resistance of mentioned alloy. For this purpose, potentio-dynamic polarization (PD) tests and electrochemical impedance spectroscopy (EIS) of ground and impacted samples were performed in 0.1 M NaCl solution at the temperature of 22±2 °C after 5 minutes of potential stabilization. The obtained PD curves were analysed using the Tafel extrapolation method and data from EIS measurements in form of Nyquist plots were quantified by the equivalent circuit method. The results showed clearly that application of the UIP significantly deteriorated corrosion resistance of AZ31 alloy in the chosen testing solution.